Genome survey sequencing of the long-legged spiny lobster Panulirus longipes (A. Milne-Edwards, 1868) (Decapoda: Achelata: Palinuridae): improved mitochondrial genome annotation, nuclear repetitive elements classification, and SSR marker discovery. Issue 1 (20th February 2022) - Baeza, J Antonio; Baker, A M; Liu, Hongtao
Abstract: The long-legged spiny lobster Panulirus longipes (A. Milne-Edwards, 1868 ) inhabits shallow water rock and coral reefs in the Indo-West Pacific region and is currently targeted by local fisheries along most of its range of distribution. This study conducted, for the first time, a genome survey in P. longipes . Using low coverage short Illumina 150 bp pair-end reads sequencing, we assembled, annotated, and manually curated the mitochondrial genome, described nuclear repetitive elements, and discovered microsatellites (SRR). The pipeline NOVOPlasty assembled the complete mitochondrial genome of P. longipes (coverage = 551×). The mitochondrial genome of P. longipes is 15, 739 bp in length and comprised of 13 protein coding genes (PCGs), 2 ribosomal RNA genes, and 22 transfer RNA genes. A single 804 bp long intergenic space is assumed to be the control region. The secondary structures of the tRNA genes exhibit a standard "cloverleaf" structure, with the exception of trnS1 that is missing the DHU arm. A large portion of repetitive sequences (~56%) was detected in the nuclear genome of P. longipes and many repetitive elements could not be assigned to known families. Taking into account only annotated repetitive elements, the most common belong to Class I-Long Interspersed Nuclear Element (LINE) and Satellite DNA which are considerably more abundant than Class I-Penelope and Class I-LTR Ty3-gypsy elements. Three clusters were classified as 45S rDNA. A total of 18 SSRs were identified. These newly developed genomic resources will contribute to clarifying the putative existence of cryptic species or subspecies, developing conservation plans, and managing the fishery of the long-legged spiny lobster Panulirus longipes .